[Tis012 (H20) 24] Cls.HCl.7H20 AS A SOURCE OF TITANIUM FOR PRE ARITH ZEOLITE TITANIUM SILlKA T (TS-l) - Sutrisno, Hari (Jurnal Penelitian Saintek, 2015)
Titanium silicate of MFJ type (TS-J) has been synthesised by usingtetrapropyl ammonium hydroxide (TPAOH) as organic template, tetraethyl orthosilicate (TEOS) and [Ti80J] (H]O)uJCI8.HCI.7H]O as silicon and titanium source respectively by hydrothermal method, The’ zeolites have been characterised by using various well-known techniques such as X-Ray Diffraction (XRD) with WinPlotr Program, Scanning Electron Microscopy (SEM) with Electron Diffraction (ED), IR and Raman spectroscopy. The zeolite of TS-J crystallises in the,orthorhombic system, space group Pnma, with a = 20.044 A;b = 19.929 A; c = J3.400 A; a = p = y = 90°. It has been changed bycalsination (TS-JC) in the monoklinik sytem, space group P2/n.J.J, with a = 20.068 A; b = J9.897 A; c = J 3.389 A, a = 90,024°; B> r= 90°.